Quartz: Deposits, Mineralogy and Analytics - Götze, Jens.; Möckel, Robert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The book will include contributions of the state of the art of quartz raw materials (deposits and properties) and their analytics. The chapters are presented by leading scientists in the quartz field. The presentations cover the main interrelations between genesis of quartz - formation of specific properties - analytics - industrial applications of SiO2 raw materials.
Classification, mineralogy and industrial potential of SiO2 minerals and rocks -- Assessment of High Purity Quartz Resources -- Quality requirements of quartz sand in the building industry.-Petrological and chemical characterisation of high-purity quartz deposits with examples from Norway -- Evaluation of the potential of the pegmatitic quartz veins of the Sierra de Comechigones (Argentina) as a source of high purity quartz by a combination of LA-ICP-MS, ICP, cathodoluminescence, gas chromatography, fluid inclusion analysis, Raman and FTIR spectroscopy -- Brazilian quartz deposits and a perspective about industrial use, gemstone and color treatment -- First-principles calculations of the E'1 center in quartz: Structural models, 29Si hyperfine parameters and association with Al impurity -- Gamma-Irradiation Dependency of EPR and TL-Spectra of Quartz -- Analysis of low element concentrations in quartz by electron microprobe.-In situ analysis of trace elements in quartz using laser ablation inductively coupled plasma mass spectrometry -- Cathodoluminescence microanalysis of the defect microstructures of bulk and nanoscale ultrapure SiO2 polymorphs for device applications -- Trace element characteristics, luminescence properties and real structure of quartz -- Mineralogy, geochemistry and cathodoluminescence of authigenic quartz from different sedimentary rocks -- CL textures and trace elements in hydrothermal quartz -- Quartz regeneration and the use of quartz as a carrier of genetic information.
Keywords: Mineralogy; Mineral resources; Geochemistry; Mineralogy; Mineral Resources; Geochemistry